Prosecuting maritime piracy : domestic solutions to international crimes - Scharf, Michael P.; Newton, Michael A.; Sterio, Milena (Cambridge University Press, 2015)
"This book addresses maritime piracy by focusing on the unique and fascinating issues arising in the course of domestic piracy prosecutions, from the pursuit and apprehension of pirates to their trial and imprisonment. It examines novel matters not addressed in other published works, such as the challenges in preserving and presenting evidence in piracy trials, the rights of pirate defendants, and contending with alleged pirates who are juveniles. A more thorough understanding of modern piracy trials and the precedent they have established is critical to scholars, practitioners, and the broader community interested in counter-piracy efforts, as these prosecutions are likely to be the primary judicial mechanism to contend with pirate activity going forward"--